Center-Pivot-Irrigated Dry-Edible Beans - O'Brien, Daniel M.; Sartwelle III, James D. (My University, 1995)
This publication projects a budget that reflects expected income and costs based on typical center-pivot-irrigated dry-edible bean production practices in western Kansas.
MF998_1995_10
Keywords: MF999; Economics; Crops; MF